Efectividad de una solución irrigante en el manejo de absceso periapical crónico: reporte de un caso - Morales-Lastre, Cristian Camilo (2023)
The endodontic environment has optimal conditions for the growth of microorganisms that can release by-products into the periapical region of the tooth and cause inflammatory lesions. Chemical disinfection using irritants solutions plays an clinical important role, as they are able to remove waste from contaminated organic and inorganic tissues, generating a residual antibacterial effect. The purpose of this study was to show the effectiveness of 2.5% and 5.25% sodium hypochlorite as an irrigating agent for the clinical management of a chronic periapical abscess in a tooth with apical resorption. Initially, 2.5% sodium hypochlorite was used, however, as it did not have an optimal abscess healing response after 3 days, it was decided to use a concentration of 5.25% to achieve a better bactericidal effect. After 5 days, the fistula healed, and endodontic treatment continued. One of the perspectives of this case report is to investigate more about the use of antibiotic therapy in conjunction with a good irrigation protocol.